1992
DOI: 10.7863/jum.1992.11.1.1
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of Doppler umbilical artery velocimetry in identifying fetal acidosis. A comparison with fetal biophysical profile

Abstract: In 105 singleton pregnancies in which cesarean section was performed before the onset of labor, the efficacy of Doppler umbilical velocimetry in identifying fetal acidosis was determined and compared with fetal biophysical profile. Doppler velocimetry showed a significant correlation with the umbilical artery pH and was also a sensitive indicator of fetal acidosis, comparable to the biophysical profile score. Patients were classified T he fetal biophysical profile (nonstress test, fetal breathing movements, fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Given this new approach to the deteriorating fetus, the other fetal surveillance tests must be re‐evaluated in order to define their clinical role. Several studies have compared NST24, 25 and biophysical profile26, 27 with Doppler for assessment in FGR. CST has several absolute (previous classic Cesarean section, placenta previa and abruptio placentae) and relative (preterm labor, cervical incompetence and preterm high‐order multiple pregnancies) contraindications and is not as well tolerated as the other fetal surveillance tests.…”
Section: Discussionmentioning
confidence: 99%
“…Given this new approach to the deteriorating fetus, the other fetal surveillance tests must be re‐evaluated in order to define their clinical role. Several studies have compared NST24, 25 and biophysical profile26, 27 with Doppler for assessment in FGR. CST has several absolute (previous classic Cesarean section, placenta previa and abruptio placentae) and relative (preterm labor, cervical incompetence and preterm high‐order multiple pregnancies) contraindications and is not as well tolerated as the other fetal surveillance tests.…”
Section: Discussionmentioning
confidence: 99%
“…Most clinical guidelines advocate combination of clinical findings, laboratory tests and ultrasound findings to make decisions on delivery in patients with preeclampsia 29 . Moreover, poor postnatal outcomes are varied and cord blood pH is considered the most objective method of assessing post-natal outcome 30 .…”
Section: Discussion:-mentioning
confidence: 99%
“…This suggests that absence or reversal of diastolic flow in the umbilical artery is associated with the worst fetal outcome in the form of increased number of IUFD Various studies have shown that the risk of perinatal morbidity and mortality increases up to 60%, with increasing severity from reduced to reversed end-diastolic flow velocity. 14,15 Rochelson B, in his study of 151 high risk pregnancies found that all the cases in which there was absent end diastolic flow had adverse perinatal outcome and all delivered or died before 37 weeks and delivered babies spent more time in NICU. 16 Perinatal mortality was remarkably high at 40% in that study.…”
Section: Discussionmentioning
confidence: 99%